2008
DOI: 10.1111/j.1574-6941.2008.00592.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiology of phototrophic iron(II)-oxidizing bacteria: implications for modern and ancient environments

Abstract: Phototrophic iron(II) [Fe(II)]-oxidizing bacteria are present in modern environments and evidence suggests that this metabolism was present already on early earth. We determined Fe(II) oxidation rates depending on pH, temperature, light intensity, and Fe(II) concentration for three phylogenetically different phototrophic Fe(II)-oxidizing strains (purple nonsulfur bacterium Rhodobacter ferrooxidans sp. strain SW2, purple sulfur bacterium Thiodictyon sp. strain F4, and green sulfur bacterium Chlorobium ferrooxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
177
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
2

Relationship

3
7

Authors

Journals

citations
Cited by 189 publications
(185 citation statements)
references
References 50 publications
8
177
0
Order By: Relevance
“…Water samples for quantification of ferrous and ferric iron were immediately acidified with 1 M HCl. Fe(II) and total Fe (Fe tot ) were quantified spectrophotometrically by the ferrozine assay, as described previously (26). Samples for quantification of dissolved ions by ion chromatography were collected in 50-ml Falcon tubes and analyzed on a Dionex DX-120 ion chromatograph equipped with an autosampler, an AS23 anion column, and a CS 12A cation column.…”
Section: Methodsmentioning
confidence: 99%
“…Water samples for quantification of ferrous and ferric iron were immediately acidified with 1 M HCl. Fe(II) and total Fe (Fe tot ) were quantified spectrophotometrically by the ferrozine assay, as described previously (26). Samples for quantification of dissolved ions by ion chromatography were collected in 50-ml Falcon tubes and analyzed on a Dionex DX-120 ion chromatograph equipped with an autosampler, an AS23 anion column, and a CS 12A cation column.…”
Section: Methodsmentioning
confidence: 99%
“…Thiodictyon sp. strain f4 displays the fastest rates of iron oxidation of all phototrophic iron-oxidizing bacteria that have been isolated (Hegler et al, 2008). Interestingly, Widdel et al (1993) reported that none of the authenticated Thiodictyon spp.…”
Section: Phototrophic Iron-oxidizing Proteobacteriamentioning
confidence: 99%
“…Soluble Fe was measured before and after sub-culturing by taking liquid samples anoxically using an N 2 flushed syringe, filtered through a 0.2 mm regenerated cellulose filter (Sartorius, G€ ottingen Germany) and transferred into 0.5 M HCl (trace metal grade, HN53.1, Carl Roth, Karlsruhe, Germany) (Sztejrenszus et al 2016). Fe 2C was measured following the ferrozine assay (Stookey 1970;Hegler et al 2008) with modifications (50% w:v ammonium acetate, 0.1% w:v ferrozine).…”
Section: Incubation Experimentsmentioning
confidence: 99%